PULP: A short biography of the banished book, Volume 1 of 5 (Singapore; Rock Paper Fire, 2016)
This publication is the first of five books, and it marks the first instalment of Pulp: A short biography of the banished book, a ten-year art project by Shubigi Rao.
English
Keywords: N7560-8266 Visual Arts. Special subjects of art